Dye-sensitized solar cell performance of a cobalt(III/II) redox mediator with the 4,5-diazafluoren-9-one ligand - Erden, Ibrahim; Faideci, Melike Arslan; Erdonmez, Seda (SPRINGER, 2018)
The development of redox shuttles containing electrolytes is very important for obtaining efficient dye-sensitized solar cells (DSSCs). We have therefore synthesized and characterized homoleptic [Co(dafo)(3)](3+/2+) complexes (dafo = 4,5-diazafluoren-9-one) and studied the effect of the redox diffusion coefficient on the photovoltaic performance of their DSSCs. The compounds were characterized by FTIR, UV-Vis spectroscopy, NMR and MS spectroscopic data. The [Co(dafo)(3)](2+/3+) system has been used to formulate redox-mediator electrolytes for application in DSSC devices with the N719 ruthenium-polypyridyl dye, TiO2 and CdS sensitizer. This system shows a slightly higher power-conversion efficiency (eta = 0.30%) in a DSSC device prepared with a CdS/Pt electrode. Although the [Co(dafo)(3)](3+/2+) electrolyte shows a moderately high open-circuit potential (V (oc) = 0.58), it suffers from a reduced short-circuit current (J (cs) = 2.04). The data suggest a decreased turnover of the Co-III/II redox couple at the Pt counter electrode for the [Co(dafo)(3)](3+/2+) system, concomitant with an increased resistance to mass-transfer diffusion.
Keywords: ORGANIC-DYES; COMPLEXES; SHUTTLES; FILMS; Chemistry